ChemInform Abstract: Synthesis of 4‐Membered Carbasugars by Way of Stereoselective SmI2‐Mediated Aldehyde—Alkene Cyclization. Issue 48 (26th November 2013) - Nocquet, Pierre‐Antoine; Hazelard, Damien; Gruntz, Guillaume; Compain, Philippe
Abstract The key step for the synthesis of new carbasugars is reported wherein cyclobutanes with four contiguous asymmetric centers are generated with a high level of stereocontrol.